2001
DOI: 10.1508/cytologia.66.409
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine-Induced Autotetraploid in Aloe vera L.

Abstract: Summary Autotetraploid plants of Aloe vera L. were induced by colchicine treatment. Diploid shoot tips (2n =2x=14) were treated by immersion of the rhizomes in colchicine concentrations of 0.05%, 0.10% and 0.15% at exposure times of 6, 12, 18 and 24 h. The highest proportion of polyploid plants (5.9%) with 2n=4x=28 was obtained from a 0.15% colchicine and 24 h combination. Diploid/tetraploid chimerical plants were observed at the lowest colchicine concentration/time treatments. Expression of gigantism in morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
4
6
0
2
Order By: Relevance
“…In contrast, the density of stomata in this species decreased by almost one-third [104]. Comparable results and relationships have been reported for tetraploid plants with medicinal properties, e.g., in Trachyspermum ammi L. [105], Aloe vera L. [106], Catharanthus roseus (L.) G Don [107], as well as energy plants, such as S. viminalis [75], P. tomentosa [82], M. sacchariflorus and M. sinensis [52] or hybrids 84K Populus alba × Populus glandulosa [77].…”
Section: Species Morphological Traits Ploidy Referencessupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, the density of stomata in this species decreased by almost one-third [104]. Comparable results and relationships have been reported for tetraploid plants with medicinal properties, e.g., in Trachyspermum ammi L. [105], Aloe vera L. [106], Catharanthus roseus (L.) G Don [107], as well as energy plants, such as S. viminalis [75], P. tomentosa [82], M. sacchariflorus and M. sinensis [52] or hybrids 84K Populus alba × Populus glandulosa [77].…”
Section: Species Morphological Traits Ploidy Referencessupporting
confidence: 73%
“…In addition, they displayed increased CO 2 assimilation and a rapid increase in biomass production [75]. Slower growth rates, especially in the early stages, may be due to slower rates of cell division, reduced metabolic rate or lower amounts of growth hormones, among other things [106]. Tetraploids with initial slow growth may include, for example, A. vera [106], A. sativum [112], S. viminalis [75] or E. purpurea [117].…”
Section: Species Morphological Traits Ploidy Referencesmentioning
confidence: 99%
“…Las plántulas (hijuelos) de Kalanchoe daigremontiana, se recolectaron de una planta madre, adquirida en el municipio de Villa del Rosario de Norte de Santander (Colombia). Se tomaron 60 hijuelos, con una altura promedio de 1 cm y un sistema radicular desarrollado (Imery y Cequea, 2001). Posteriormente, en cámara oscura las plántulas fueron sometidas a diferentes concentraciones (0,025 y 0,1%: p/v) y tiempos de exposición (24 y 48 h) con colchicina, tomando como control el agua destilada (Tab.…”
Section: Materials Vegetal Y Condiciones Del Cultivounclassified
“…Tomatillo autotetraploids had higher values for leaf width and flower diameter compared to diploid, coinciding with Cequea (2000) who mentions that autopolyploids have a wider ecological tolerance and larger cell sizes, meanwhile Imery and Cequea (2001) found that new tetraploid genotypes of A. vera produced greater leaf biomass accumulation, especially due to the increase in width and thickness of the leaves, also, Rego et al (2011) found that with the formation of autotetraploid of Passiflora edulis Sims. (2n= 2x= 18) using colchicine and oryzalin obtained more vigorous plants (2n= 2x= 36).…”
Section: Resultados Y Discusión Caracterización Morfológicamentioning
confidence: 57%